Modelling peak accelerations from earthquakes. - Dupuis, Debbie J.
This paper deals with the prediction of peak horizontal accelerations with emphasis on seismic risk and insurance concerns. Non-linear mixed effects models are used to analyse well-known earthquake data and the consequences of mis-specifying assumptions on the error term are quantified. A robust fit of the usual model, using recently developed robust weighted maximum likelihood estimators, is presented. Outlying data are automatically identified and subsequently investigated. A more appropriate model accounting for the extreme value nature of the responses, is also developed and implemented. The implication on acceleration predictions is demonstrated.
Keywords: Earthquake; Peak horizontal accelerations; Seismic risk assessment; Non-linear mixed- effects models; Partially non-linear mixed-effects models; Weighted maximum likelihood; Robust estimation; Generalized extreme value distribution